2017
DOI: 10.1038/s41598-017-01469-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of insulin clearance in apparently healthy non-obese Japanese men

Abstract: Hyperinsulinemia observed in obese subject is caused at least in part by low metabolic clearance rate of insulin (MCRI). However, the determinants of MCRI in non-obese subjects are not fully understood. To investigate the correlates of MCRI in healthy non-obese men (BMI <25 kg/m2), we studied 49 non-obese Japanese men free of cardiometabolic risk factors. Using a 2-step hyperinsulinemic euglycemic clamp, we evaluated MCRI and insulin sensitivity. We also calculated the rate of glucose disappearance (Rd) during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
(72 reference statements)
4
24
0
Order By: Relevance
“…In our cohort of healthy and non‐obese participants, we found that insulin MCR correlated significantly with several adverse metabolic parameters, such as total body fat mass, fat mass percentage and glucose Rd/SS Ins . Similar findings have also been reported in healthy and non‐obese Japanese individuals with low insulin MCR. Thus, the lower insulin MCR could represent the initial event in the natural history of IR and obesity pathogenesis among Indian individuals.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our cohort of healthy and non‐obese participants, we found that insulin MCR correlated significantly with several adverse metabolic parameters, such as total body fat mass, fat mass percentage and glucose Rd/SS Ins . Similar findings have also been reported in healthy and non‐obese Japanese individuals with low insulin MCR. Thus, the lower insulin MCR could represent the initial event in the natural history of IR and obesity pathogenesis among Indian individuals.…”
Section: Discussionsupporting
confidence: 85%
“…These metabolic parameters have not been adequately studied in non‐obese Indians and Chinese. Similarly, hyperinsulinemia and the impaired insulin metabolic clearance rate (MCR) might be a harbinger of worsenining IR and future cardiometabolic disorders, even in healthy individuals with non‐obese BMI. However, the influence of impaired insulin MCR on metabolic health in these two ethnic groups remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…1), supporting a link between hepatic insulin clearance and hepatic insulin sensitivity. An inverse association between insulin clearance and basal as well as insulin-suppressed hepatic glucose production has also been demonstrated in cross-sectional studies (46).…”
Section: Hepatic Fat Content and Insulin Clearancementioning
confidence: 70%
“…When insulin resistance was induced by dietary fat, normal dogs responded by enhancing b-cell function by approximately 20% and reducing insulin clearance by approximately 50%; the decreased insulin clearance preceded b-cell compensation (48). Therefore, decreased insulin clearance is hypothesized to be an important compensatory mechanism for insulin-resistant states, such as type 2 diabetes, as it reduces the burden on b-cells to produce additional insulin (49,50). In our study, ghrelin, with or without Ex9, decreased meal-related insulin clearance and insulin sensitivity (OGIS) compared with saline.…”
Section: Salinementioning
confidence: 99%